ANALISIS TINDAK TUTUR ILOKUSI PADA NASKAH DRAMA ARIFIN C. NOER YANG BERJUDUL “A-A, I-I, U-U” - Dhiiya Nafiisa Muflihani; Any Budiarti; Marlia (STKIP Subang, 2023)
Language plays an important role in social communication between speakers and listeners. Through language, opinions, thoughts, and ideas can be easily expressed and understood by others. In communicative interactions, speech acts play a crucial role as they involve actions within the communication. However, speakers and listeners often face difficulties in understanding the context of a conversation. One important aspect of speech acts is the illocutionary meaning contained within them. Speech acts can occur in various everyday life situations, both in oral and written forms. A script of a drama is an example of a written form of speech acts, where utterances serve as the main foundation of a conversation. This research employs a descriptive qualitative research method to examine illocutionary speech acts in the context of written language, focusing on the use of language in Arifin C. Noer's drama script titled